The Reward of the Pharaohs: Egyptian royal grants and gifts for the rulers of Canaan in the Amarna letters - Abo-Eleaz, Mohy-Eldin E. (Antiguo Oriente, 2021)
The Reward of the Pharaohs: Egyptian Royal Grants and Gifts for the Rulers of Canaan in the Amarna Letters The present study explores and analyzes the grants and gifts awarded by the Pharaohs to the Canaanite rulers through a variety of evidence from the Amarna letters. This analysis considers the reasons for requesting or granting—whether from the sender or the receiver—in political, ideological, economic, and social terms. The study reveals that the request for gifts was not exclusively between the Great Kings, the methods of requesting/exchanging gifts between Pharaohs and their vassals was similar to that between the Pharaohs and the other Great Kings of the Near East. The study also concludes that providing grants and exchanging gifts took place under the policy of persuasion and reciprocal exploitation, according to the Egyptian and Levantine perspectives. Egypt was the side that benefitted most from this exchange in accordance with the concepts of sovereignty and domination because it was one of the most efficient methods that kept these vassals’ loyalty to Egypt at the lowest costs.